Visualization programs bolster simulations - Mathias, Don (R & D : reading for the R & D community, 2003)
A vast number of research applications require scientists to model or visualize complex concepts and relationships in order to better understand the fundamental intricacies within a data set. Gordon Erlebacher at the School of Computational Science and Information Technology at Florida State University selected Amira and AmiraDev from TGS, San Diego. The team has cited three important benefits to the software: isosurfaces were quite vivid, the flowchart paradigm was much easier to use, and Amira was the only package that made extensive use of texture-based algorithms.